Good in a Room - Palmer, Stephanie (Tantor Media, 2008)
Business consultant and former MGM director of creative affairs Stephanie Palmer reveals the techniques used by Hollywood's top writers, producers, and directors to get financing for their projects and explains how you can apply these techniques to be more successful in your own high-stakes meetings. Because, as Palmer has found, the strategies used to sell yourself and your ideas in Hollywood not only work in other businesses, they often work better . Whether you are a manager or executive with an innovative proposal, a professional with a hot concept, a salesperson selling to a potential client or investor, or an entrepreneur with a business plan, Good in a Room shows you how to: - Master the five stages of the face-to-face meeting - Avoid the secret deal breakers of the first ninety seconds - Be confident in high-pressure situations - Present yourself better and more effectively than you ever have before Whether you want to ask for a raise, grow your client list, launch a new business, or find financing for a creative project, you must not only present your ideas in a compelling way - you must also sell yourself. Good in a Room shows you how to construct a winning presentation and deliver the kind of performance that will get your project greenlighted, whatever industry you are in.